Medicine and the media: Medical experts' problems and solutions while working with journalists. - Anna Larsson; Susanna Appel; Carl Johan Sundberg; Mårten Rosenqvist (PLoS ONE, 2019)
Medical experts are one of the main sources used by journalists in reporting on medical science. This study aims to 1) identify problems that medical experts encounter in contacts with the media representatives, 2) elucidate their attitudes about interactions with journalists and 3) reflect on solutions that could improve the quality of medical journalism. By using in-depth interviews, focus groups and a survey directed to 600 medical experts in 21 countries, this cohort study elucidates medical experts' experiences and views on participating in popular media. A strong interest in interacting with the media was identified among the experts, where nearly one fifth of the respondents in the survey claimed that they contacted the media more than 10 times per year. Six obstacles for improving the quality of medical reporting in the media were found: deadlines, headlines, choice of topic or angle, journalist's level of medical knowledge, differences in professional culture and colleagues' opinions. The main concern among experts was that short deadlines and exaggerated headlines could harm journalistic quality. It is possible that this is partly due to ongoing changes in the media landscape with many new platforms and less control functions. Nevertheless, for several reasons many experts have great interest in interacting with the media, something that could contribute to better communication and fewer misunderstandings. Our results highlight factors like expert networks, media training for scientists and regular meetings that may facilitate communication between medical experts and medical reporters.